2015
DOI: 10.1038/ng.3322
|View full text |Cite
|
Sign up to set email alerts
|

Common variants at 10p12.31, 10q21.1 and 13q12.13 are associated with sporadic pituitary adenoma

Abstract: Pituitary adenoma is one of the most common intracranial neoplasms, and its genetic basis remains largely unknown. To identify genetic susceptibility loci for sporadic pituitary adenoma, we performed a three-stage genome-wide association study (GWAS) in the Han Chinese population. We first analyzed genome-wide SNP data in 771 pituitary adenoma cases and 2,788 controls and then carried forward the promising variants for replication in another 2 independent sets (2,542 cases and 3,620 controls in total). We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 44 publications
2
26
1
1
Order By: Relevance
“…In that study, two markers on chromosome 10 and one on chromosome 13 were associated with elevated PA risk in the Han Chinese population. With ORs ranging from 1.28 to 1.44, these SNPs have modest influence on increased risk for PA development (19). Even www.eje-online.org…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, two markers on chromosome 10 and one on chromosome 13 were associated with elevated PA risk in the Han Chinese population. With ORs ranging from 1.28 to 1.44, these SNPs have modest influence on increased risk for PA development (19). Even www.eje-online.org…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that a wider range of clinically significant adenomas tend to aggregate in families (18). The genetic mechanisms underlying common forms of adenoma are less clear, with multiple genes potentially involved in the pathogenicity of PA. A recent genome-wide association study identified two markers on chromosome 10 and one on chromosome 13 to the presence of sporadic mutations in the Han Chinese population (19). A novel finding suggests Xq26.3 microduplication responsible for sizeable proportion of the infantile pituitary gigantism cases, and further examination of the genes in this region in sporadic acromegaly cases suggests GPR101 as a cause (20).…”
Section: Introductionmentioning
confidence: 94%
“…The association test of PNPLA3 SNPs (rs1010023, rs738409), demographic (age, sex), anthropometric (height, weight, hipline, and waistline), and biochemical parameters (TBIL, DBIL, AST, ALT, GGT, ALP, INS, FBG, TC, TG, HDL, LDL, UA, and BUN), was carried out by logistic regression using PLINK v1.07 [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
“…Pituitary adenoma is the third most common primary intracranial tumor of the central nervous system (Nakamura et al, 2011;Ye et al, 2015), as well as the most common saddle area tumor (Qu et al, 2011). Pituitary adenomas are benign tumors, but some have shown the ability to invade areas outside of the central nervous system, such as the intracranial region, which can lead to serious health problems and even death (Trouillas et al, 2003;Norberg et al, 2012;Palumbo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%